Asuhan Kebidanan Komprehensif pada Ny S Umur 27 Tahun G2P1A0 dengan Riwayat Sectio Caesarea (SC) dan Cephalopelvic Disproportion (CPD) di BPM Ny. S di wilayah Kerja Puskesmas Kaliwadas Kabupaten Brebes Tahun 2023 - Maya Aufia Sabila; Himatul khoeroh; Sri Nurhayati (Jurnal Siti Rufaidah, 2024)
Maternal Mortality Rate (MMR) is the number of maternal deaths during pregnancy or within 42 days after the end of pregnancy from any cause related to pregnancy during a certain time per 100,000 live births (World Bank, 2021). The maternal mortality rate (MMR) worldwide according to the World Health Organization (WHO) in 2020 is 295,000 deaths with the causes of maternal death being high blood pressure during pregnancy (pre-eclampsia and eclampsia), bleeding, postpartum infections, and unsafe abortion (WHO , 2021). According to ASEAN data, the highest MMR was in Myanmar at 282.00/100,000 KH in 2020 and the lowest MMR was in Singapore in 2020. There were no maternal deaths in Singapore (ASEAN Secretariat, 2021). According to the Indonesian Ministry of Health (2020), the number of MMR in Indonesia in 2020 was 4,627 cases and in 2021 it increased to 6,865 cases (Media Indonesia, 2021). The maternal mortality rate in Indonesia is still quite high. From data from the Kaliwadas Health Center, maternal deaths were caused by bleeding, pneumonia, pulmonary TB, hemorrhagic shock. And there are various factors that can cause the most maternal deaths in Indonesia, namely bleeding, hypertension in pregnancy, bleeding disorders, CPD, history of SC (Ministry of Health of the Republic of Indonesia, 2020).Objective: Able to provide comprehensive services according to service standards in pregnancy care, childbirth, postpartum, postpartum, family planning.Research methods : This research uses a qualitative descriptive method with a field observational case study approach. Results: Based on the comprehensive midwifery care provided to Mrs. N, 27 years old with a history of caesarean section (SC) and cephalopelvic disproportion (CPD), Mrs. S with the first visit to the fourth visit with a diagnosis of CPD so action had to be taken with (SC). In the care of newborns up to 28 days no problems were found and during the postpartum period no problems were found. Mrs. S chose implantable birth control contraception. Conclusion: Appropriate care provided by midwives during pregnancy, childbirth, newborns, postpartum and family planning is very important for the health of mothers and babies.